Fairness and Frictions: The Impact of Unequal Raises on Quit Behavior - Arindrajit Dube; Laura Giuliano; Jonathan Leonard (Institute for the Study of Labor (IZA), 2015)
We analyze how quits responded to arbitrary differences in own and peer wages using an unusual feature of a pay raise at a large U.S. retailer. The firm's use of discrete pay steps created discontinuities in raises, where workers earning within 1 cent of each other received new wages that differed by 10 cents. First, we estimate a regression discontinuity (RD) model based on own wages; we find large causal effects of wages on quits, with quit elasticities less than -10. Next, we address whether the overall quit response reflects the impact of comparisons to market wages or to the wages of in-store peers. Here we use a multi-dimensional RD design that includes both a sharp RD in the own wage and a fuzzy RD in the average peer wage. We find that the large quit response mostly reflects relative-pay concerns and not market comparisons. After accounting for peer effects, quits do not appear to be very sensitive to wages consistent with the presence of significant search frictions. Finally, we find that the relative-pay effect is nonlinear and driven mainly by workers who are paid less than their peers suggesting concerns about fairness or disadvantageous inequity.
Keywords: J00; J31; J42; J63; 330; turnover; search frictions; fairness; quits; peer effects; regression discontinuity